Robert Young Pelton's the world's most dangerous places Afghanistan - Drachkovitch, Rasha; Keane, David (Discovery Channel, 2005)
"Robert Young Pelton journeys into one of the world's most dangerous places to meet one of the world's most mysterious and elusive leaders: Ahmed Shah Massoud, the Lion of Panjshir. In a spectacular land torn by war for three decades, the enigmatic leader of Afghanistan's Northern Alliance fights the oppressive Taliban regime from the remote, rugged mountains outside of the capital of Kabul. On his adventure, Pelton discovers the way in which war shapes countries and transforms the destiny of a besieged yet noble people"--Container.